Effects of prolonged standing on ground reaction force control and core muscle activation - Soliday, Kylie M., author; Reiser, Raoul F., II, advisor; Browning, Ray, committee member; Gilkey, David, committee member (Colorado State University. Libraries, 2015)
Prolonged standing (PS) is a common activity that is becoming more recommended in the work place. However, there’s a strong association between PS and low back pain (LBP) with up to 81% of individuals reporting LBP after 2 hours or less on their feet. There is also a noted sex difference with this LBP development during PS, with women experiencing LBP with a higher frequency than men, while men report higher pain levels of LBP than women. The specific factors involved, and sex related differences are not fully understood. One potential factor may be bilateral asymmetries in posture. The goal of this study was to examine the effect of PS on bilateral weight-bearing, ground reaction force (GRF) control (i.e., center of pressure (CoP)) and core muscle activation within healthy young adult men and women during quiet stance (QS). Twenty-four healthy, pain-free subjects (12 men, 12 women) voluntarily participated in the study (age = 22.3 ± 2.4 years, height = 1.70 ± 0.09 m, mass = 69.89 ± 11.31 kg, BMI = 24.1 ± 2.5 kg/m2 [mean ± SD]). Subjects performed two 60 second QS trials (pre-PS & post-PS) separated by one 30 minute free standing trial while bilateral GRFs under each foot and surface electromyography (sEMG) of each lumbar erector spinae (ES), gluteus medius (GM), internal obliquus (IO), and external obliquus (EO) were measured. Muscle activity was normalized to a submaximal reference contraction (%ref). Sway, maximum velocity (maxV), and path length (PL) were calculated from the CoP for both the dominant (D) and non-dominant (ND) foot, as well as net combined values. All CoPs were calculated in both the anterior-posterior (AP) and medial-lateral (ML) directions, and were normalized to standing height (%height). Weight-bearing (WBAs), muscle activation (MAAs), and CoP asymmetries (CoPAs) were calculated by subtracting the ND limb from their D limb using the symmetry index (%SI) equation. There were no differences in WBAs, MAAs, or CoPAs between the pre-PS and post-PS trials, nor between the men and the women (p≥0.058). However, there was an increase in the net PL (both AP and ML), AP sway, and ML maxV after PS exposure (p≤0.003). With CoP movements, generally the ND limb was a greater contributor than the D limb for both of the QS trials. For the pre-PS trial, the ND limb had greater ML PL, AP PL, ML maxV, and AP maxV (p≤0.032), while sway did not show significant difference between the two limbs in either the ML or AP directions (p≥0.585). ML PL, AP PL, and AP maxV was greater for the ND limb (p≤0.001), while ML sway, AP sway, and ML maxV did not significantly differ between the limbs for the post-PS trial (p≥0.084). During the pre-PS trial, there was a significant correlation between the WBAs and the GM asymmetry for the women (p=0.044, r=0.615) but not the men (p=0.259, r=0.354). This correlation was not significant during the post-PS trial for either sex (p≥0.176, r≤0.418). Significant negative correlations were found between WBAs and CoPAs during the pre-PS trial for the ML sway and ML PL variables for the women (p≤0.019, r≤-0.660), and ML PL and ML maxV variables for the men (p≤0.018, r≤-0.666). During the post-PS trial, these significant correlations (also negative) were present for the ML sway, ML PL, AP PL, and AP maxV variables for the women (p≤0.024, r≤-0.644), and ML PL, AP maxV, and ML maxV variables for the men (p≤0.029, r≤-0.628). There were no significant correlations found between the absolute WBAs and net CoP movements for both of the QS trials, as well as for both sexes (p≥0.082, -0.521≤r≤0.461) The women had overall higher GM activity than the men (women = 7.6 ± 3.4 %ref, men = 4.8 ± 2.9 %ref; p=0.041). Overall ES activity decreased from the pre-PS to the post-PS trial for the men, but not the women (women = 2.1 ± 1.0 %ref, pre-PS men = 2.6 ± 1.8 %ref, post-PS men 1.8 ± 1.5 %ref; p=0.002). While these results suggest that 30 minutes of PS does not have an effect on WBAs, MAAs, or CoPAs during QS in healthy young adults, there appears to be an effect on net CoP movements, as well as sex related differences in both muscle activity and change in muscle use. Previous studies have indicated fatigue causing increased CoP movements, which suggests that PS may also be inducing low levels of fatigue. There has also been indication that men and women have differences in hip muscle activation strategies, which could be reflected in the GM activity findings. The decrease in ES activity from pre-PS to post-PS that was recorded in men and not women is possibly related to men having higher relative percentages of the more fatigable type II muscle fibers in the ES. These findings shed light on why men and women may respond differently to PS.
Keywords: movement; prolonged; asymmetry; standing; muscle